Using microalgae to produce liquid transportation biodiesel: What is next?. (October 2017) - Zhu, Liandong; Nugroho, Y.K.; Shakeel, S.R.; Li, Zhaohua; Martinkauppi, B.; Hiltunen, E.
Abstract: In response to the energy crisis, global warming and climate changes, microalgae have received increasingly global attention as a renewable, alternative and sustainable source for the production of biodiesel. Much original research regarding microalgal biodiesel production has been reported. However, microalgal biodiesel faces plenty of challenges that current cultivation and biodiesel conversion is economically unfeasible for industrial applications on a large scale. This perspective paper first briefly discusses the latest advances in liquid transportation biodiesel production from microalgal biomass, including microalgal growth, biomass harvesting and drying, lipid extraction and biodiesel conversion. Subsequently, strategies for the future development of microalgal biodiesel have been proposed and discussed, in an attempt to reduce the cost gap. From the microalgal biodiesel production chain perspective, genetic and metabolic engineering, isolation of suitable species, high-efficiency bioreactor development, efficient culturing system development, optimal harvest process design, high-efficiency lipid extraction and transesterification method development will have critical roles to play. It is worthy of note that the increase of the outcome credits can also realize the reduction of the economic gap, and the main measures include appropriate glycerol recovery and reutilization, integration with wastewater treatment and CO2 mitigation together with microalgal biorefinery for the production of multiple co-products with high values. Finally, concluding remarks are put forward.